2012
DOI: 10.1089/lap.2012.0129
|View full text |Cite
|
Sign up to set email alerts
|

Incisional Hernia Rate May Increase After Single-Port Cholecystectomy

Abstract: Although single-port cholecystectomy seems to be a feasible surgical technique, it is not superior over the traditional laparoscopic cholecystectomy. Single-port cholecystectomy is equal to laparoscopic cholecystectomy with respect to conversion to open surgery, postoperative hospital stay, and operative time, but it is associated with high hospital cost and high port-site hernia rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 24 publications
5
34
1
Order By: Relevance
“…Additionally, SPS patients might need to be followed longer in order not to miss incisional hernias. This latter finding was also supported by another study on SPS [10].…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, SPS patients might need to be followed longer in order not to miss incisional hernias. This latter finding was also supported by another study on SPS [10].…”
Section: Discussionsupporting
confidence: 82%
“…It has been argued against single port laparoscopy that there could be a higher rate of incisional hernia. [26][27][28][29][30][31] We did not find any such difference, and we actually believe that it is easier to close the fascial wound after single port laparoscopy because the larger skin incision facilitates the closing. Longer follow-up time should in any case be employed to re-evaluate whether incisional hernia rates continue to be equal in both groups.…”
Section: Discussionmentioning
confidence: 64%
“…According to Alptekin et al, SILC was not superior to traditional laparoscopic cholecystectomy. Technical difficulties such as the inability to work comfortably in the limited anatomical area, the proximity of the trocars, superposition of the instruments, and poor ergonomics were the main reasons stated [5,10]. The results of some clinical studies have also supported this conclusion.…”
Section: Discussionmentioning
confidence: 97%
“…The closed environment of the umbilicus region increases the risk of secretion and infection around the incision in patient groups operated with multi-channel devices. Bunting reports that hernia development is most common in the umbilicus among the trocar insertion sites (88.9%) [5,[22][23][24]. Although actual rates are not known, Alptekin et al found the frequency of port site hernia development after the SILC technique to be about 3.2 times higher than the LC technique [5].…”
Section: Post-operative Complicationsmentioning
confidence: 99%